2019
DOI: 10.1039/c8cp06971a
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved multirotational dynamics of single solution-phase tau proteins reveals details of conformational variation

Abstract: Time-resolved fluorescence anisotropy reveals conformational variation of single tau proteins in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…33 These steps must be implemented quickly enough to overcome the diffusive motion of the particle, and significant recent progress has been made toward optimizing this control loop to enable trapping of individual small organic fluorophores. 28,34 Trap implementations that utilize either intrinsic or label-based fluorescence to track emissive particles have been employed to characterize time-varying photophysical states, [35][36][37][38][39][40] molecular dynamics and kinetics, [41][42][43][44][45][46][47] and more. [48][49][50] However, the trapping duration, and therefore data collection, in anti-Brownian traps is typically limited by photobleaching or by blinking because dark particles cannot be tracked and are quickly lost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 These steps must be implemented quickly enough to overcome the diffusive motion of the particle, and significant recent progress has been made toward optimizing this control loop to enable trapping of individual small organic fluorophores. 28,34 Trap implementations that utilize either intrinsic or label-based fluorescence to track emissive particles have been employed to characterize time-varying photophysical states, [35][36][37][38][39][40] molecular dynamics and kinetics, [41][42][43][44][45][46][47] and more. [48][49][50] However, the trapping duration, and therefore data collection, in anti-Brownian traps is typically limited by photobleaching or by blinking because dark particles cannot be tracked and are quickly lost.…”
mentioning
confidence: 99%
“…All implementations of anti-Brownian traps can be distilled to two essential aspects of the closed-loop feedback: first, real-time tracking provides the location of a particle relative to the target position and may be determined using fluorescence , or bright- or dark-field imaging ,, in combination with either camera-based tracking or timed movement of the excitation beam and one or more point detectors. ,, Second, a feedback force must be quickly applied to move the particle back toward the target, which may be implemented using electric fields to induce electrophoresis or electroosmosis, thermal gradients to induce thermophoresis, optical forces, or differential pressure to induce hydrodynamic flow . These steps must be implemented quickly enough to overcome the diffusive motion of the particle, and significant recent progress has been made toward optimizing this control loop to enable trapping of individual small organic fluorophores. , Trap implementations that utilize either intrinsic or label-based fluorescence to track emissive particles have been employed to characterize time-varying photophysical states, molecular dynamics and kinetics, and more. However, the trapping duration and associated data collection in anti-Brownian traps are typically limited by photobleaching or blinking because dark particles cannot be tracked and are quickly lost. Bechhoefer and co-workers successfully demonstrated trapping of nonfluorescent particles using a dark-field signal, but the unfavorable scaling of scattering intensity with particle size limits this approach to relatively large nanoscale objects (>100 nm) with large scattering cross sections.…”
mentioning
confidence: 99%
“…Upon closer examination of the R ee distributions for each replicate, it appears that P 13 samples two conformational states (Figure g): a behavior that has interestingly been observed in other IDPs. , For instance, the time-resolved fluorescence anisotropy measurements of tau, an IDP linked to Alzheimer’s disease, exhibit a bimodal distribution indicative of more and less compact conformational families . Oftentimes, the stability of these heterogeneous sub-populations is attributed to peptidyl-prolyl cis/trans isomerization: an interconversion that occurs on timescales too slow to be observed in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Transient β-structures can be formed in the R2 and R3 regions at the level of two hexapeptide motifs, termed PHF6* and PHF6 (VQIINK and VQIVYK, respectively) [168]. Anisotropy studies [169] revealed that tau monomers can reside in at least two different conformations, with the two hexapeptides either exposed or buried. However, even within these conformations, different tau strains can emerge, as observed in monomers derived from AD and corticobasal degeneration patients' brains [170].…”
Section: Tau and Tauopathiesmentioning
confidence: 99%